2016
DOI: 10.3390/biology5010013
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Functional Insights into the Integrated Regulation of Innate Immune Cell Responses by Teleost Leukocyte Immune-Type Receptors

Abstract: Across vertebrates, innate immunity consists of a complex assortment of highly specialized cells capable of unleashing potent effector responses designed to destroy or mitigate foreign pathogens. The execution of various innate cellular behaviors such as phagocytosis, degranulation, or cell-mediated cytotoxicity are functionally indistinguishable when being performed by immune cells isolated from humans or teleost fishes; vertebrates that diverged from one another more than 450 million years ago. This suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 114 publications
(176 reference statements)
0
11
0
Order By: Relevance
“…A deeper understanding of the intracellular signal transduction pathways initiated by LILRA2 or LILRA6 is required to understand how they activate immune-related gene expression. Moreover, LILRA genes (LILRA1, 3 and 5) has been shown to play an important role in innate immune responses through regulation of the ERK/MEK [ 15 ], TLR [ 3 , 39 ] and JNK/p38MAPK [ 16 ] signaling pathways, as well as the antigen-presenting phenotype and cytokine production [ 3 , 6 , 9 ]. Increased expression levels of phosphorylated STAT1, STAT3 and JAK2 and un-phosphorylated STAT1/3, JAK2 and TYK2 molecules in response to LILRA2 and LILRA6 transfected in HD11 cells were detected by western blot and FACS analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deeper understanding of the intracellular signal transduction pathways initiated by LILRA2 or LILRA6 is required to understand how they activate immune-related gene expression. Moreover, LILRA genes (LILRA1, 3 and 5) has been shown to play an important role in innate immune responses through regulation of the ERK/MEK [ 15 ], TLR [ 3 , 39 ] and JNK/p38MAPK [ 16 ] signaling pathways, as well as the antigen-presenting phenotype and cytokine production [ 3 , 6 , 9 ]. Increased expression levels of phosphorylated STAT1, STAT3 and JAK2 and un-phosphorylated STAT1/3, JAK2 and TYK2 molecules in response to LILRA2 and LILRA6 transfected in HD11 cells were detected by western blot and FACS analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LILRAs have been demonstrated to play important roles in infection or autoimmune diseases such as HIV infection [ 11 ], multiple sclerosis [ 12 ], atopic dermatitis [ 13 ] and rheumatoid arthritis [ 14 ]. It has been reported that LILRA1, 3, 4 and 5 bind with HLA-G, HLA-C and classical HLAs [ 3 , 7 , 11 , 13 , 14 ] and regulate adaptive or innate immune pathways such as the ERK/MEK [ 15 ], TLR [ 3 ] and JNK/p38MAPK [ 16 ] signaling pathways. Additionally, they have been reported to upregulate the cytokines IL-1R, IL-4, IL-6, IL-10, IL-12, IL-17, TNFα and IFN-γ [ 3 , 7 , 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that IpLITR 1.1b can uniquely network with intracellular components requisite for the production of F-actin containing filopodia-like structures. Previously, we hypothesized that IpLITR 1.1b-controlled signaling events induce formation of macromolecular complexes with its CYT that pre-assemble prior to receptor engagement; effectively priming the receptor for subsequent interactions with extracellular targets ( 28 30 ). Pre-associations of IpLITR 1.1b with intracellular effectors capable of modulating the cytoskeletal machinery would allow for dynamic membrane remodeling events prior to the formation of stable receptor–ligand interactions ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The following day cells were washed with phosphate buffered saline (PBS) and then incubated in phagocytosis buffer (1:1 mixture of 1× PBS containing 2 mg/mL bovine serum albumin, Sigma-Aldrich) and 1× Opti-MEM reduced serum medium (Fisher Scientific Company) containing 9 × 10 5 4.5-µm target microspheres (beads; Polybead ® Carboxylate YG microspheres; Polysciences, Warrington, PA, USA) opsonized with 10 µg/mL of αHA mAb (Cedarlane Laboratories Ltd., Burlington, ON, Canada) or 10 µg/mL of the isotype control mouse IgG3 (Beckman Coulter, Mississauga, ON, Canada). Antibody opsonization was performed by absorbing them onto protein A precoated microspheres (isolated from Staphylococcus aureus ; Sigma-Aldrich) as previously described ( 28 , 29 ). Plates containing cells and target beads were then centrifuged at 1,500 rpm for 1 min to synchronize cell–bead interactions and then incubated for 1 h at either 27 or 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation